Common Features in Overtrained Athletes and Individuals with Professional Burnout: Implications for Sports Medical Practice - Selänne, H.; Ryba, T. V.; Leppäluoto, J. (Athletic Insight Journal, 2013)
In ihis paper, the authors discuss the sympioms of overtraining and burnout— two syndromes in which the etiology, after the decades of research, is Still poorly understood. Overtraining is caused by an imbalance between exercise and rest, and often triggered by increased neuromuscular loading. There are no reliable diagnostic tests for overtraining. The neurological mechanisms underpinning burnout are similarly not known; however, it is generally accepted that the main cause is mental overloading. Both conditions are stress-related developmental processes suggesting malfunction of adrenal cortex and hypothalamus, mainly the pituitary. The two syndromes are also related to a variety of individual, environmental, and organizational factors. Based on the first author's extensive practical experience of working with overtrained athletes and individuals with occupational burnout, the authors draw on both literatures to offer invaluable insights into a medical assessment and treatment of athletes suffering from overtraining.